Investigation of performance of free-piston engine generator with variable-scavenging-timing technology under unsteady operation condition. (September 2021) - Cheng, Ziwen; Jia, Boru; Xin, Zhenfang; Feng, Huihua; Zuo, Zhengxing; Smallbone, Andrew; Roskilly, Anthony Paul
Highlights: A numerical model of free-piston engine generator in Simulink and BOOST is presented. Scavenging efficiency and performance with fixed scavenging progress is analyzed. Unsteady working condition could affect the scavenging efficiency and performance. Variable-scavenging-timing technology is recommended with unsteady working condition. Abstract: A substantial number of free-piston engine generators still use cross scavenging, which limits scavenging quality and performance under unsteady condition. Variable-scavenging-timing technology is a novel method to change the fixed scavenging process so that the scavenging process is coordinated with piston movement. This paper investigated effects of the variable-scavenging-timing technology implemented on the free-piston engine generator. In designed case that the free-piston engine generator has different compression ratios, cyclic variation and frequency, the variable-scavenging-timing technology improved the scavenging quality and performance. The delivery ratio of the free-piston engine generators applied with the variable-scavenging-timing technology decreased about 0.3 at different compression ratios, 0.18 at different cyclic variations and 0.2 at different frequencies on average. The trapping efficiency of FPEG rose over 70% and the scavenging efficiency was maintained at least 85%. As for different compression ratios, the power increased by an average of 0.18 kW. While the power was improved 0.2 kW on average under the other condition. The increase of indicated efficiency had an increase varying from 1% to 2% compared with before. The changes of the performance about free-piston engine generators under different unsteady condition also were discussed.